Numerical and Experimental Study of Friction Damping Blade Attachments of Rotating Bladed Disks - D. Charleux; C. Gibert; F. Thouverez; J. Dupeux (International Journal of Rotating Machinery)
In order to mitigate high cycle fatigue risks in bladed disks, the prediction of the vibration levels early in the design process is important. Therefore, the different sources of damping need to be modeled accurately. In this paper the impact of friction in blade attachments on forced response is investigated both numerically and experimentally. An efficient multiharmonic balance method is proposed in order to compute the forced response of bladed disks with contact and friction nonlinearities in blade roots. For experimental validation purposes, a rotating bladed disk was tested in a vacuum chamber, with excitation being provided by piezoelectric actuators. A model of the rig was built and numerical results were obtained with a normal load dependent coefficient of friction and a constant material damping ratio. Nonlinear behavior observed experimentally at resonances was well reproduced and an acceptable correlation was found with experimental resonant frequencies, amplitudes, and amount of damping throughout the spinning speed and excitation level range. The proposed numerical method can therefore serve to enhance the prediction of the alternating stresses in bladed disk assemblies.